Governmental and regulatory aspects of irrigated urban vegetable farming in Ghana and options for its institutionalization - Drechsel, Pay; Obuobie, Emmanuel; Adam-Bradford, A.; Cofie, Olufunke O. (2014)
This chapter examines key institutional issues that are important to the recognition and sustainability of irrigated vegetable farming in Ghanaian cities. It assesses the informal nature of the business and examines current roles being played by relevant agencies directly or indirectly linked to urban vegetable farming and urban wastewater management. The chapter also looks at relevant bylaws, strategies and policies that have implications for the recognition of informal irrigation and/or the adoption of safety measures for risk reduction in irrigated vegetable farming. It also suggests options to facilitate the institutionalization of irrigated urban agriculture.